Analysis of the relationship of economic inequality to criminality in the city of South Tangerang - Agung Widjaya; Aryobimo Daniswara; Cindy Patricia; Farel Gunawan; Michelle Soewandi; Noviana Putri Buntoro; Verlyana Agustien Hodyanto; Zhafira Wafa Ariella (Privietlab, 2021)
the relationship between economic growth and income inequality can be positive and negative. In low-income developing countries, there is a negative relationship between income inequality and economic growth, in contrast to high-income developing countries, which have a positive relationship between inequality and economic growth. The findings from the research we did the economic inequality variable and the crime rate variable in the South Tangerang City area have a significant relationship. Based on the results of the field research studies that we have done, we can provide suggestions that can be used by related parties, with the aim of improving the quality of the economy and reducing the crime rate in the South Tangerang area. As explained in the research above that there is a significant influence between economic inequality and the crime rate so that we think the government can provide jobs that can improve the quality of the economy in the South Tangerang City area so that the economic level in the South Tangerang area can be better and the level of crime can be reduced.